PAPRICA: The Pair Production Imaging Chamber—Proof of Principle - Toppi, M.; Avanzolini, I.; Balconi, L.; Battistoni, G.; Calvi, G.; De Simoni, M.; Dong, Y.; Fantoni, A.; Franciosini, G.; Marafini, M.; Fischetti, M.; Muccifora, V.; et al. (Frontiers in Physics, 2021)
In Particle Therapy, safety margins are applied around the tumour to account for the beam range uncertainties and ensure an adequate dose coverage of the tumour volume during the therapy. The reduction of safety margins is in great demand in order to diminish the particle therapy side effects especially in the case of treatment of tumours close to organs at risk and of pediatric patients. To this aim, beam range monitoring techniques are being developed by the scientific community, most of all based on the detection of secondary particles produced by the nuclear interactions of the beam with the patient's tissue nuclei. In this contribution, a novel beam range monitoring technique is proposed, based on the detection of prompt photons exploiting the pair production mechanism. The proof of principle of the PAir PRoduction Imaging ChAmber (PAPRICA) is studied through the development of a Monte Carlo simulation and the detector performances in a clinical scenario are determined.